2010
DOI: 10.1007/s00436-010-2083-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protein-free defined media, and effect of l-cysteine and ascorbic acid supplementation on viability of axenic Entamoeba histolytica

Abstract: Entamoeba histolytica is the etiologic agent for amoebiasis. The excretory-secretory (ES) products of the trophozoites contain virulence factors and antigens useful for diagnostic applications. Contaminants from serum supplements and dead trophozoites impede analysis of ES. Therefore, a protein-free medium that can sustain maximum viability of E. histolytica trophozoites for the longest time duration will enable collection of contaminant-free and higher yield of ES products. In the present study, we compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The protein-free media (RPMI-C-A) used in this experiment has previously been shown to support 95% viability of E. histolytica trophozoites for up to 8 h [21]. Nevertheless, there may still be a small number of dead E. histolytica trophozoites that were lysed and released proteins into the medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein-free media (RPMI-C-A) used in this experiment has previously been shown to support 95% viability of E. histolytica trophozoites for up to 8 h [21]. Nevertheless, there may still be a small number of dead E. histolytica trophozoites that were lysed and released proteins into the medium.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatant was then pooled and centrifuged at 10,000× g for 5 min at 4 °C and filtered through 0.2 µm filter (Sartorius Stedim, Germany). Subsequently, the supernatant was concentrated 1000 times using a spin filter with 5 kDa molecular-weight cut off (Vivapsin, Sartorius), and a cocktail of protease inhibitors (Roche, Germany) was added [20]. Protein samples and RPMI-CA medium (concentrated 100X, as control) were reduced with 0.284 M β-mercaptoethanol by boiling for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, iodoacetamide was added to the RPMI-C-A medium containing the ESA upon its collection in order to protect the protein from degradation by proteases (3,13,15). Although we have previously optimized the growth conditions of E. histolytica trophozoites so that ϳ 95% of the parasites were alive when ESA was collected (20), nevertheless it is still possible that some of the antigenic bands may have come from ruptured trophozoites.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the cell density was determined via the trypan blue exclusion method. Trophozoites were seeded into a culture tube 80% filled with RPMI-C-A medium at a cell density of 0.8 ϫ 10 6 cells per ml and incubated at 36°C for 6 h. Using this method, we have previously shown that ϳ95% trophozoite viability can be maintained throughout the incubation period (20). Upon completion, culture tubes were subjected to centrifugation at 22 ϫ g for 2 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation